Safety and efficacy of minimally invasive surgery plus alteplase in intracerebral haemorrhage evacuation (MISTIE): a randomised, controlled, open-label, phase 2 trial - Hanley, Daniel F; Thompson, Richard E; Muschelli, John; Rosenblum, Michael; McBee, Nichol; Lane, Karen; Bistran-Hall, Amanda J; Mayo, Steven W; Keyl, Penelope; Gandhi, Dheeraj; Morgan, Tim C; Ullman, Natalie; et al. (Lancet neurology, 2016)
Craniotomy, according to the results from trials, does not improve functional outcome after intracerebral haemorrhage. Whether minimally invasive catheter evacuation followed by thrombolysis for clot removal is safe and can achieve a good functional outcome is not known. We investigated the safety and efficacy of alteplase, a recombinant tissue plasminogen activator, in combination with minimally invasive surgery (MIS) in patients with intracerebral haemorrhage. MISTIE was an open-label, phase 2 trial that was done in 26 hospitals in the USA, Canada, the UK, and Germany. We used a computer-generated allocation sequence with a block size of four to centrally randomise patients aged 18–80 years with a non-traumatic (spontaneous) intracerebral haemorrhage of 20 mL or higher to standard medical care or image-guided MIS plus alteplase (0·3 mg or 1·0 mg every 8 h for up to nine doses) to remove clots using surgical aspiration followed by alteplase clot irrigation. Primary outcomes were all safety outcomes: 30 day mortality, 7 day procedure-related mortality, 72 h symptomatic bleeding, and 30 day brain infections. This trial is registered with ClinicalTrials.gov, number NCT00224770. Between Feb 2, 2006, and April 8, 2013, 96 patients were randomly allocated and completed follow-up: 54 (56%) in the MIS plus alteplase group and 42 (44%) in the standard medical care group. The primary outcomes did not differ between the standard medical care and MIS plus alteplase groups: 30 day mortality (four [9·5%, 95% CI 2·7–22.6] vs eight [14·8%, 6·6–27·1], p=0·542), 7 day mortality (zero [0%, 0–8·4] vs one [1·9%, 0·1–9·9], p=0·562), symptomatic bleeding (one [2·4%, 0·1–12·6] vs five [9·3%, 3·1–20·3], p=0·226), and brain bacterial infections (one [2·4%, 0·1–12·6] vs zero [0%, 0–6·6], p=0·438). Asymptomatic haemorrhages were more common in the MIS plus alteplase group than in the standard medical care group (12 [22·2%; 95% CI 12·0–35·6] vs three [7·1%; 1·5–19·5]; p=0·051). MIS plus alteplase seems to be safe in patients with intracerebral haemorrhage, but increased asymptomatic bleeding is a major cautionary finding. These results, if replicable, could lead to the addition of surgical management as a therapeutic strategy for intracerebral haemorrhage. National Institute of Neurological Disorders and Stroke, Genentech, and Codman.